Smart cities on the waterfront: citizens' perspectives on smart city in the context of a port city - Edelman, Kristel; Franzen, Riikka; Wahlström, Irina; Tsvetkova, Anastasia; Chen, Yiran (Slovenia, 2025)
This paper explores how smart city is defined by citizens in the context of a port city, and which aspects are prominent due to the significant role of a ferry port in such cities. Through a case study of a port city comprising a survey of its citizens, this research investigates citizens’ perceptions of a smart city, contextualised in the actual use of the area close to the port and expectations towards the development of this area. Utilizing thematic analysis of survey data, key themes identified include traffic, environmental sustainability, technology and digitalization, and the importance of focusing on people, their wellbeing and quality of life. The findings emphasise the citizens’ wish for prioritising environmental sustainability and wellbeing in the development of the smart city in a context of a port city and show that improvements in traffic around the port area and urban planning are seen as most topical.
37th Bled eConference - Resilience Through Digital Innovation : Enabling the Twin Transition